The Economics of The Market for Pirated Media: A Cross-Country Study - Wood, Luke (2006)
This paper investigates if economic theory can explain the factors which make consumers choose between pirated and original (legitimate) goods. It is demonstrated that economic theory explains much of the individual variation in a survey study. This study was carried out on a global scale, and studies differences between developed and developing economies. Availability, corruption, risk of prosecution are just some of the variables found to influence the purchase, and number of purchases of pirated media. The study illustrates that a major factor influencing the purchase of pirated goods, is the belief that they are being over charged. It is demonstrated that calculating the price elasticity of demand, and lowering the price to a level the consumer is happy with, may defeat the pirates, and even increase profits in some of these industries.